Self-Assembled Nanogels Based on Ionic Gelation of Natural Polysaccharides for Drug Delivery - Wang, Huimin; Deng, Hong; Gao, Menghan; Zhang, Weiqi (Frontiers in Bioengineering and Biotechnology, 2021)
The polysaccharides (PS) have been widely used as biomaterials in drug delivery, due to their excellent biocompatibility, ease of functionalization, and intrinsic biological activities. Among the various PS-based biomaterials, the self-assembled PS nanogels (NG) featuring facile preparation are attracting evergrowing interests in various biomedical applications. Specifically, NG derived from the self-assembly of natural PS well maintain both the physicochemical and biological properties of PS while avoiding the chemical modification or alteration of PS structure, representing a potent drug delivery system for various therapeutic agents. In this review, the natural PS, such as chitosan, alginate, and hyaluronan, for self-assembled NG construction and their advantages in the applications of drug delivery have been summarized. The residues, such as amine, carboxyl, and hydroxyl groups, on these PS provide multiple sites for both ionic cross-linking and metal coordination, which greatly contribute to the formation of self-assembled NG as well as the drug loading, thus enabling a wide biomedical application of PS NG, especially for drug delivery. Future developments and considerations in the clinical translation of these self-assembled PS NG have also been discussed.